PELATIHAN E-COSAL BAGI GURU-GURU SMP N 1 KEDUNGWUNI PEKALONGAN - Rizka Hayati; Ida Ayu Panuntun; Erwan Kustriyono (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2022)
One of the implementations of 2013 curriculum in the learning process is the Scientific Approach. The stages of implementing the scientific approach are observing, asking, associating, reasoning, testing, processing, formulating and presenting. During pandemic situation like this, the learning process takes place online. Whether teachers like it or not, it is required them to change the habit of teaching face to face with online learning. Several challenges and problems emerged in the teaching and learning process, one of them was difficulty of applying scientific approach methods in online learning. This was also experienced by the teachers of SMP N 1 Kedungwuni Pekalongan. The teachers have difficulty in applying scientific approach in learning process and have not maximized the use of online learning applications. Based on the problem above, PKM team provided a solution, the solution was E-COSAL training for teachers of SMP N 1 Kedungwuni Pekalongan. The training was carried out in several steps, namely socialization, training, mentoring, and evaluation. After PKM activity was held, the teachers of SMP N 1 Kedungwuni Pekalongan, were able to improve their knowledge and skills, especially in the application of scientific approaches online and also the operation of E-COSAL. Keywords : E-COSAL, Scientific Approach, Socialization, Training; Mentoring, evaluation